The intersection of environmental racism and conservation: a systematic review of publications affiliated with UCT that deal with race and environmental sustainability - Rathmell, Sophie G (Department of Environmental and Geographical Science, 2022)
The following research explores the intersection of environmental racism and conservation in literature affiliated with the University of Cape Town, through the means of a systematic review. This systematic review is contextualised by not only the socio-economy of Cape Town and the greater South Africa, but also the self-positioning of UCT as an ‘anchor institution' that is impactful, though its research, on the wider community. The research sorts a total of 81 publications into nine themes, timeboxed by the past 10 years. This study is limited only to peer-reviewed journal articles published in English, in established journals. The results indicate growth in the number of publications on these topics over the decade, with the most being published in 2018, 2019, and 2020, and uncovered that the publications offer a significant amount of critique on the environmental governance in the global south, and in South Africa specifically. Through a deep analysis, this research identifies trends across publications, from the year of publication, the current events at the time of writing, and the range that the various authors explore. The study shows that there is a lack of publications on the implementation of the proposed solutions or strategies that tackle the deeply complex issue of eradicating racism, and building a sustainable future for everyone, particularly in the developing world. This research provides a comprehensive review of affiliated literature with UCT on these topics, while identifying gaps in the publications. It identifies spaces where, if time and resources became available, UCT could collaborate and help implement strategies and policies, above and beyond research and recommendations.